Three-Day Continuous Oxytocin Infusion Attenuates Thermal and Mechanical Nociception by Rescuing Neuronal Chloride Homeostasis via Upregulation KCC2 Expression and Function - Ba, Xiyuan; Ran, Chenqiu; Guo, Wenjun; Guo, Jing; Zeng, Qian; Liu, Tao; Sun, Wuping; Xiao, Lizu; Xiong, Donglin; Huang, Yelan; Jiang, Changyu; Hao, Yue (Frontiers in Pharmacology, 2022)
Oxytocin (OT) and its receptor are promising targets for the treatment and prevention of the neuropathic pain. In the present study, we compared the effects of a single and continuous intrathecal infusion of OT on nerve injury-induced neuropathic pain behaviours in mice and further explore the mechanisms underlying their analgesic properties. We found that three days of continuous intrathecal OT infusion alleviated subsequent pain behaviours for 14 days, whereas a single OT injection induced a transient analgesia for 30 min, suggesting that only continuous intrathecal OT attenuated the establishment and development of neuropathic pain behaviours. Supporting this behavioural finding, continuous intrathecal infusion, but not short-term incubation of OT, reversed the nerve injury-induced depolarizing shift in Cl− reversal potential via restoring the function and expression of spinal K+-Cl- cotransporter 2 (KCC2), which may be caused by OT-induced enhancement of GABA inhibitory transmission. This result suggests that only continuous use of OT may reverse the pathological changes caused by nerve injury, thereby mechanistically blocking the establishment and development of pain. These findings provide novel evidence relevant for advancing understanding of the effects of continuous OT administration on the pathophysiology of pain.